(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
Indonesia, and in order evaluate genetics diversity of mangosteen and their close relatives, we employed isoenzyme and AFLP marker on 13 accessions of mangosteen and their close relatives. Isoenzyme marker using four enzyme systems produced 25 bands and 88% out of them were polymorphic and elucidate genetic variability at similarity level ranged between 0.38-0.89. AFLP markers with three primer system produced 220 polymorphic bands and revealed genetic variability at similarity level ranged between 0.38-0.89 successfully produced high polymorphism bands and elucidates genetic variability at similarity coefficient ranged between 0.21-0.77. Both markers exhibited similar clustering pattern, and group successfully G. mangostana accessions in one clustering group. Furthermore G. malaccensis and G. porrecta consistently showed closer genetic relationship to G. mangostana clustering group in both markers, in comparison to G. hombroniana, which implies the assumption they may be the progenitor of G. mangostana, and should be reviewed with more accurate data. Â© 2009 Biodiversitas, Journal of Biological Diversity Key words: genetic diversity, mangosteen, isozymes, AFLP.